The role of liver transplantation in the care of primary hepatic vascular tumours in children - Grimaldi, Chiara; de Ville de Goyet, Jean; Bici, Kejd; Cianci, Maria Chiara; Callea, Francesco; Morabito, Antonino (Frontiers in Oncology, 2022)
Liver transplantation (LT) is the standard of care for many liver conditions, such as end-stage liver diseases, inherited metabolic disorders, and primary liver malignancies. In the latter group, indications of LT for hepatoblastoma and hepatocellular carcinoma evolved and are currently available for many non-resectable cases. However, selection criteria apply, as the absence of active metastases. Evidence of good long-term outcomes has validated the LT approach for managing these malignancies in the context of specialist and multidisciplinary approach. Nevertheless, LT’s role in treating primary vascular tumours of the liver in children, both benign and malignant, remains somewhat controversial. The rarity of the different diseases and the heterogeneity of pathological definitions contribute to the controversy and make evaluating the benefit/risk ratio and outcomes quite difficult. In this narrative review, we give an overview of primary vascular tumours of the liver in children, the possible indications and the outcomes of LT.